+0  
 
0
250
1
avatar

b(5px - 3c) = a(qx - 4)

Guest Aug 20, 2017
 #1
avatar+178 
0

Input: b(5px-3c) = a(qx-4)

Intepretation: Solve for \(x\) in \(\)\(b(5px+3c) = a(qx-4)\)

Expand:

\(5bpx-3bc=aqx-4a\)

Move the \(x\) terms to the right, integer ones to the left:

\(5bpx-aqx=3bc-4a\)

Pull the x out from the left term:

\((5bp-aq)x=3bc-4a\)

Divide both sides by \(5bp-aq\):

\(x=\frac{3bc-4a}{5bp-aq}\)

Done :D

Jeffes02  Aug 20, 2017

27 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.